1982
DOI: 10.1093/ije/11.3.268
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis Markers in Roman Children

Abstract: A random sample of sera from children admitted over a 23-month period to a large paediatric hospital in Rome for diagnoses believed unrelated to viral hepatitis, was tested for HBsAG, anti-HBs, anti-HBc and anti-HAV. No sex or area of residence differences were found. The prevalence for markers of prior hepatitis B infection in children aged 1-12 years was 6.5%, in agreement with other observations in Italy and European countries. Prevalence of anti-HAV among children age 1-12 admitted for diagnoses believed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…The prevalence of 4-2% found in this study is less than that found in 340 patients (age 1-12 years), admitted to a paediatric hospital in Rome in 1982 (6-5%) (Pasquini et al 1982). On the other hand, incidence of hepatitis B seems to be decreasing (Mele et al 1990) and the prevalence resulting from the present study is in accordance with the 4-7% prevalence shown in a study of Sardinian adolescents (Stroffolini et al 1990).…”
Section: Discussioncontrasting
confidence: 74%
“…The prevalence of 4-2% found in this study is less than that found in 340 patients (age 1-12 years), admitted to a paediatric hospital in Rome in 1982 (6-5%) (Pasquini et al 1982). On the other hand, incidence of hepatitis B seems to be decreasing (Mele et al 1990) and the prevalence resulting from the present study is in accordance with the 4-7% prevalence shown in a study of Sardinian adolescents (Stroffolini et al 1990).…”
Section: Discussioncontrasting
confidence: 74%